2023
DOI: 10.1097/j.pain.0000000000002926
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for a core outcome measurement set for clinical trials in whiplash associated disorders

Abstract: Inconsistent reporting of outcomes in clinical trials of treatments for whiplash associated disorders (WAD) hinders effective data pooling and conclusions about treatment effectiveness. A multidisciplinary International Steering Committee recently recommended 6 core outcome domains: Physical Functioning, Perceived Recovery, Work and Social Functioning, Psychological Functioning, Quality of Life and Pain. This study aimed to reach consensus and recommend a core outcome set (COS) representing each of the 6 domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In a recent article, Sterling et al discussed the inconsistency of reporting of outcomes in clinical trials of treatments for WAD. 118 They suggested the lack of consistency reduced opportunities for data pooling and therefore conclusions regarding the efficacy of treatments. To address this, a steering committee developed a set of core outcomes in six different domains which included psychological functioning, quality of life, and work and social functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent article, Sterling et al discussed the inconsistency of reporting of outcomes in clinical trials of treatments for WAD. 118 They suggested the lack of consistency reduced opportunities for data pooling and therefore conclusions regarding the efficacy of treatments. To address this, a steering committee developed a set of core outcomes in six different domains which included psychological functioning, quality of life, and work and social functioning.…”
Section: Discussionmentioning
confidence: 99%
“… 119 The authors recommend that the instruments identified in this process should be used as standard in all clinical trials examining the effectiveness of interventions for WAD. 118 Similar attention to the scope and consistency of outcome measure used in other MSK injury treatment interventions (eg, MSK/orthopaedic trauma rehabilitation) settings is desirable.…”
Section: Discussionmentioning
confidence: 99%